Some characteristics of 3,7-dinitro-, 3,7-dinitroso- and dinitrate compounds derived from 1,3,5,7-tetraazabicyclo[3.3.1]nonane - Vágenknecht, Jirí; Zeman, Svatopluk (Journal of hazardous materials, 2005)
The paper presents a set of some literature data and the authors' own experimental results of stability, sensitivity and explosion parameters of energetic Mannich N-bases, 3,7-dinitro-1,3,5,7-tetraazabicyclo[3.3.1]nonane (DPT), 3,7-dinitroso-1,3,5,7-tetraazabicyclo[3.3.1]nonane (DNPT) and hexamethylenetetramine dinitrate (HEXADI). Both their chemical and thermal reactivities are discussed. The results of small-scale cook-off test, determination of initiation ability, detonation velocity, impact sensitivity and performance show that the lowest process safety risks are connected with HEXADI.
Keywords: bezpečnost; Explosions; hodnocení rizik; alkany; Nitroso Compounds; exploze; Safety; Alkanes; nitrososloučeniny; Risk Assessment